Antibiotic treatment alleviates red mark syndrome symptoms in rainbow trout (Oncorhynchus mykiss) and reduces load of Midichloria-like organism - Schmidt, Jacob Günther; Henriksen, Niels Henrik; Olesen, Niels Jørgen (Aquaculture, 2021)
Red mark syndrome (RMS) is a skin disease of rainbow trout, the prevalence of which has increased in Europe over the last two decades. Hallmark symptoms are large, haemorrhagic skin lesions. It is believed that the disease is bacterial and caused by a Midichloria-like organism (MLO). However, the bacterium has never been isolated or cultured in vitro, and is only known from its 16S rDNA sequence. Thus there is no vaccine for the disease, and no other officially recognized way of ameliorating RMS symptoms. Here we investigate for the first time the effect on RMS of in-feed treatment with three types of antibiotics: Florfenicol, oxolinic acid and oxytetracycline under controlled experimental conditions using a cohabitation model of disease transfer. In short, 160 rainbow trout were cohabited with seeder fish, which showed the classical skin pathology of RMS and tested positive for MLO. After 55 days at 12 °C the cohabitants (now weighing 223 ± 57 g) started showing very early signs of RMS-related skin pathology and were randomly divided into 8 tanks (4 treatment groups in duplicate). The fish were fed medicated (or control) feed for 10 days. The fish were evaluated visually after 7 and 14 days and finally terminated after 20 days where skin samples were taken for testing for MLO by qPCR. All three types of antibiotics significantly affected the monitored disease parameters: Macroscopic skin lesions were less severe and less MLO 16S rDNA could be detected from skin samples by qPCR in antibiotics-fed fish compared to fish that had not received antibiotics. •Florfenicol, oxolinic acid and oxytetracycline all reduced RMS skin pathology.•Florfenicol, oxolinic acid and oxytetracycline all reduced MLO 16S rDNA copy numbers.•Results support existing evidence that RMS is caused by a bacterium.•Antibiotic treatment is efficient for RMS, but may have limited practical use.